Innovative Collaboration Fintech and Islamic Financial Institutions in Optimizing Islamic Philanthropy for Economic Empowerment of the Ummah - Al Kahfi; Nurfajriani, Wiyanda Vera (Yayasan Mitra Peduli Indonesia, 2025)
In the digital era, optimizing the utilization of Islamic philanthropy, such as Zakat, Infaq, Sadaqah, and Waqf (ZISWAF), is crucial for empowering the Muslim community economically. This study aims to analyze the collaborative model between Islamic financial technology (sharia fintech) and Islamic financial institutions (IFIs) in enhancing the effectiveness of Islamic philanthropic fund distribution. Using a descriptive qualitative approach and literature review, the findings reveal that synergy between these entities enables a more efficient, transparent, and sustainable system for collecting and distributing funds. Fintech is a digitalization accelerator and access expander, while IFIs ensure sharia compliance and professional fund management. This collaborative model can transform beneficiaries (Mustahiq) into donors (Muzakki), strengthen the Islamic microenterprise sector, and foster an inclusive and just Islamic financial ecosystem. The study recommends strengthening regulations, enhancing sharia digital literacy, and integrating systems between fintech and IFIs to support an Islamic philanthropy-based community economy.